Pentagon-shaped Microstrip Patch Antenna in ISM band for Hyperthermia Application - Khan A.; Singh A.K. (My University, 2025)
In this paper, a pentagon-shaped microstrip patch antenna was proposed for the Hyperthermia application. The proposed antenna operates in the ISM band of 434 MHz with a size of 120mm x 120mm x 1.6mm. FEM-based HFSS software has been used for simulation and using FR-4 substrate with relative permittivity of 4.4 and thickness of 1.6 mm. The proposed antenna structure is considered in a combined single-layer human tissue model phantom. The specific absorption rate (SAR) is achieved along the x-axis variation inside the phantoms at different distances from the antenna. © 2022 IEEE.